Design and Validity of Augmented Reality Based Student Worksheets Integrated with Acehnese Culture - Fairus; Pardomuan Sitompul; Elvis Napitupulu; Riezky Purnama Sari; Liza Fitria (Proceeding of International Conference on Multidisciplinary Research, 2024)
This research aims to design and validate student worksheets based on Aughmented Reality integrated with Acehnese culture. This research is development research using the Plomp model. This research is limited to two stages, namely preliminary research (preliminary research) and the development phase (prototyping phase). The instrument used is a student worksheet validation sheet consisting of aspects of material, presentation, language, and integration with the Augmented Reality application. Validation was carried out by 3 expert validators. Based on the problems in the initial research, the student worksheet design is integrated with Acehnese culture where Acehnese cultural ornaments become markers that will be visualized into 3D shapes. The results of the research show that the design of student worksheets based on augmented reality integrated with Acehnese culture is in the best condition with a valid category.